2012
DOI: 10.5402/2012/791383
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition Combined with Enteral Nutrition for Severe Acute Pancreatitis

Abstract: Background and Aims. Nutritional support in severe acute pancreatitis (SAP) is controversial concerning the merits of enteral or parenteral nutrition in the management of patients with severe acute pancreatitis. Here, we assess the therapeutic efficacy of gradually combined treatment of parenteral nutrition (PN) with enteral nutrition (EN) for SAP. Methods. The clinical data of 130 cases of SAP were analyzed retrospectively. Of them, 59 cases were treated by general method of nutritional support (Group I) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Rationale: Three RCTs comparing gastric with jejunal feeding in severe acute pancreatitis showed no significant differences between the 2 levels of EN infusion within the GI tract with regard to tolerance or clinical outcome 354 . ‐ 356 A meta‐analysis by Chang et al showed that there was no difference between the levels of infusion with regard to pain sensation, diarrhea, or energy balance (energy provision) 357 …”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Rationale: Three RCTs comparing gastric with jejunal feeding in severe acute pancreatitis showed no significant differences between the 2 levels of EN infusion within the GI tract with regard to tolerance or clinical outcome 354 . ‐ 356 A meta‐analysis by Chang et al showed that there was no difference between the levels of infusion with regard to pain sensation, diarrhea, or energy balance (energy provision) 357 …”
Section: Acute Pancreatitismentioning
confidence: 99%
“…During an intense workout or under conditions of hypoxia, an insufficient oxygen supply can reduce Krebs cycle reactions, produce less ATP, and enhance glycolysis, resulting in decreased removal ability of the liver and kidneys and ultimately to the accumulation of lactate in plasma [ 24 , 25 ]. The increased levels of lactate and succinic acid in the AP group were likely because of anaerobic glycolysis, which was enhanced by the increased energy consumption and oxygen deficit during early stages of AP [ 26 ]. Since lactate concentration is influenced by oxygen supply and fluid resuscitation, this elevation was not detected in urine samples from patients with pancreatitis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[57] showed that combining TPN with EN after day 4 of ICU admission in patients for whom EN is insufficient to meet their nutritional goals have reduced nosocomial infections and improved their clinical outcomes [57]. A small retrospective study showed that combined enteralparenteral nutrition in patients with severe acute pancreatitis not only can improve the natural history of pancreatitis but also can reduce the incidence of complication and mortality [58]. In another small retrospective study by Hsu et al .…”
Section: Combined En and Tpnmentioning
confidence: 99%